(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1913)
The investigation of a group of five ’Norse’ burial mounds is reported. A roughly built cist in the largest of the mounds contained nothing but earth, while the second largest mound contained cremated human bone within a steatite urn laid on a bed of charcoal. An examination of two of the smaller mounds disclosed neither cist nor urn, only ashes, fragments of bones, and some bits of round charred wood.